2012
DOI: 10.1590/s0001-37652012005000061
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies on the sporogenous tissue and anther wall of Leucojum aestivum (amaryllidaceae) in different developmental stages

Abstract: In this study, ultrastructures of anther wall and sporogenous tissue of Leucojum aestivum were investigated during different developmental stages. Cytomictic channels were seen between pollen mother cells during prophase I. Polar distribution was described in the organelle content of pollen mother cells and microspores in early phases of microsporogenesis and also in pollen mitosis. Active secretion was observed in tapetal cells. Previous reports about developmental stages of male gametophyte were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…Increase of RNA content in the middle layer and endothecium can be related with pollen nutrition. The ultrastructure of anther wall cells also justifies the results of histological observations (Ekici & Dane 2012).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Increase of RNA content in the middle layer and endothecium can be related with pollen nutrition. The ultrastructure of anther wall cells also justifies the results of histological observations (Ekici & Dane 2012).…”
Section: Discussionsupporting
confidence: 65%
“…In recently done studies in Leucojum aestivum, polarity was determined in ultrastructures of PMC (Pollen mother cells), sporogenous tissue cells and the microspores which were ready for pollen mitosis, in the distribution of organelles (Ekici & Dane 2012), in the synergids and egg cells of female gametophyte and in the active (functional) megaspore (Ekici & Dane 2008). In this study, some of the histochemical features of the anther wall in Leucojum aestivum were tried to explain during pollen development.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the sorghum anther developmental process exhibited both similarities and differences with other plant species. We have found that later stages of anther development are much alike across a broad range of different plant species while the early stages vary somewhat among different species (Sanders et al 1999 ; Zhang et al 2011 ; Ekici and Dane 2012 ; Wang et al 2012 ; Xu et al 2014 ; Tsou et al 2015 ; Browne et al 2018 ; Chaban et al 2020 ). The anther development in sorghum resembles mostly to those of maize anthers (Wang et al 2012 ; Moon et al 2013 ; Tsou et al 2015 ), followed by those in wheat and rice (Zhang et al 2011 ; Browne et al 2018 ).…”
Section: Discussionmentioning
confidence: 98%
“…the experimental samples are of high quality and the data meet the requirements, and the test data is accurate. Several studies have shown that the MFA in the annual rings near the young timber of the medullary heart is usually large, and it tends to decrease with the increase in tree age, and then remains relatively stable [23][24][25].…”
Section: Microfibril Angle (Mfa)mentioning
confidence: 99%